Standard-dose pembrolizumab in combination with reduced-dose ipilimumab for patients with advanced melanoma (KEYNOTE-029): an open-label, phase 1b trial. Issue 9 (September 2017) - Long, Georgina V; Atkinson, Victoria; Cebon, Jonathan S; Jameson, Michael B; Fitzharris, Bernie M; McNeil, Catriona M; Hill, Andrew G; Ribas, Antoni; Atkins, Michael B; Thompson, John A; Hwu, Wen-Jen; Hodi, F Stephen; et al.
Summary: Background: Reduced-dose nivolumab in combination with standard-dose ipilimumab improves objective response and progression-free survival compared with standard-dose ipilimumab alone, but increases toxicity. We assessed the safety and anti-tumour activity of standard-dose pembrolizumab in combination with reduced-dose ipilimumab. Methods: In this open-label, phase 1b trial, we recruited patients from 12 medical centres in Australia, New Zealand, and the USA. Eligible patients were aged at least 18 years, had advanced melanoma, had an Eastern Coooperative Oncology Group performance status of 0 or 1, had measurable disease according to the Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1, had adequate organ function, had resolution of toxic effects of the most recent previous chemotherapy to grade 1 or less, had no active autoimmune disease requiring systemic steroids or immunosuppressive agents, had no active non-infectious pneumonitis, had no uncontrolled thyroid dysfunction or diabetes, had no active brain metastases, and had not received previous immune checkpoint inhibitor therapy. Patients received intravenous pembrolizumab 2 mg/kg plus intravenous ipilimumab 1 mg/kg every 3 weeks for four doses, followed by intravenous pembrolizumab 2 mg/kg every 3 weeks for up to 2 years or disease progression, intolerable toxicity, withdrawal of consent, or investigator decision. The primary endpoint was safety and tolerability. The proportion of patients achieving an objective response assessed per RECIST version 1.1 by independent central review and overall survival were secondary endpoints. We also assessed progression-free survival. The primary endpoint was assessed in all patients who received at least one dose of combination therapy. Activity was assessed in all enrolled patients. This trial is registered with ClinicalTrials.gov, number NCT02089685 . Enrolment into this cohort is closed, but patients are still being monitored for safety and anti-tumour activity. Findings: Between Jan 13, 2015, and Sept 17, 2015, we enrolled and treated 153 patients. As of the Oct 17, 2016, cutoff date, median follow-up was 17·0 months (IQR 14·8–18·8). 110 (72%) of 153 patients received all four pembrolizumab plus ipilimumab doses; 64 (42%) remained on pembrolizumab monotherapy. 110 grade 3–4 treatment-related adverse events occurred in 69 (45%) patients. No treatment-related deaths occurred. Treatment-related adverse events led to discontinuation of pembrolizumab and ipilimumab in 22 (14%) patients, including 17 (11%) who discontinued both treatments for the same event and five (3%) who discontinued ipilimumab for one event and later discontinued pembrolizumab for another. 12 (8%) patients discontinued ipilimumab only and 14 (9%) discontinued pembrolizumab only because of treatment-related adverse events. 158 immune-mediated adverse events of any grade occurred in 92 (60%) patients, and 50 immune-mediated adverse events of grade 3–4 occurred in 42 (27%) patients; the most common immune-mediated adverse events were hypothyroidism (25 [16%]) and hyperthyroidism (17 [11%]). 93 (61% [95% CI 53–69]) patients achieved an objective response. Estimated 1 year progression-free survival was 69% (95% CI 60–75), and estimated 1 year overall survival was 89% (95% CI 83–93). Interpretation: Standard-dose pembrolizumab given in combination with four doses of reduced-dose ipilimumab followed by standard-dose pembrolizumab has a manageable toxicity profile and provides robust anti-tumour activity in patients with advanced melanoma. These data suggest that standard-dose pembrolizumab plus reduced-dose ipilimumab might be a tolerable, efficacious treatment option for patients with advanced melanoma. A randomised phase 2 trial of alternative dosing strategies of this combination is underway. Funding: Merck & Co, Inc.